Effect of intensive diet and exercise on self-efficacy in overweight and obese adults with knee osteoarthritis: The IDEA randomized clinical trial. Issue 2 (4th April 2018) - Mihalko, Shannon L; Cox, Phillip; Beavers, Daniel P; Miller, Gary D; Nicklas, Barbara J; Lyles, Mary; Hunter, David J; Eckstein, Felix; Guermazi, Ali; Loeser, Richard F; DeVita, Paul; Messier, Stephen P
Abstract : Older, overweight and obese adults with knee osteoarthritis, who lost weight and engaged in regular exercise viewed themselves as more capable in their ability to walk and function. Additionally, those with enhanced confidence were able to walk greater distances and experienced less pain. Abstract: Physical activity decreases the risk of osteoarthritis (OA)-related disability; however, pain and lack of confidence represent barriers for older adults with knee OA. The purpose of this study was to examine (a) the baseline associations among self-efficacy and physical activity, function, and pain; (b) longitudinal changes in self-efficacy; and (c) whether self-efficacy mediates treatment effects on clinical outcomes. The Intensive Diet and Exercise for Arthritis (IDEA) trial was a single-blind, randomized controlled 18-month study including 454 overweight/obese older adults ( M age = 66 years) with knee OA. Participants were randomized to one of three interventions: exercise (E), diet-induced weight loss (D), or both (D+E). Self-efficacy for gait, balance, and walking duration were assessed at baseline, 6 months, and 18 months. Baseline associations were tested using Pearson correlations, and group least squares means were compared using mixed linear models at follow-up. Participants with higher self-efficacy reported significantly better physical function and less knee pain at baseline, walked farther (6-min walk), and were more physically active (all |r| > 0.12, all p < .01). Significant differences between groups were detected for all self-efficacy measures at 18 months; the D+E group reported significantly (all p < .005) higher self-efficacy for gait, walking duration, and balance compared with the D- or E-only groups. Self-efficacy significantly ( p < .05) mediated treatment effects on physical function and pain at 18 months. A combined intervention of diet-induced weight loss and exercise is the treatment of choice to maximize self-efficacy, improve physical function, and reduce pain in overweight/obese adults with knee OA.